The Limits of Human Rights Oversight: Evaluating National Human Rights Commission (NHRC) Jurisdiction in Nepal (Sambahak: Human Rights Journal, 2025)
This article undertakes a comprehensive examination of the jurisdiction of Human Rights Commissions of Nepal, with a particular focus on the National Human Rights Commission (NHRC) as established under the Constitution of Nepal 2015. The research explores the evolving legal framework governing human rights protection in Nepal, tracing its development from the Human Rights Commission Act of 1997 through constitutional changes and post-conflict transitional justice mechanisms. Through doctrinal analysis of constitutional provisions, legislative frameworks, case law, and comparative jurisdictional models, this study critically evaluates the scope, limitations, and effectiveness of the Commission's mandate. Particular attention is given to jurisdictional challenges including territorial and subject-matter limitations, overlap with other constitutional commissions, implementation gaps between legal authority and practical enforcement, and the interplay between national jurisdiction and international human rights obligations. The findings reveal a complex institutional architecture with progressive formal powers but significant operational constraints. This article argues that while Nepal has established an advanced constitutional foundation for human rights protection, jurisdictional ambiguities, resource limitations, and political interference continue to impede the Commission's effectiveness. Recommendations include legislative clarification of overlapping mandates, enhanced enforcement mechanisms, greater institutional independence, and the harmonization of domestic jurisdiction with international obligations to strengthen Nepal's human rights protection framework.